The Effects of Marketization of Long-term Care Services for Older Adults in Korea. Issue 45 (8th August 2019) - Chon, Yongho
Abstract: To cope with the rapid increase in aging population, the South Korean government introduced new long-term care insurance in 2008 by using the market forces and mechanisms of competition and choice. The study explored the effect of the marketization of long-term care (LTC) services on the provision of services under the Korean long-term care insurance (LTCI) system. By adopting qualitative semi-structured in-depth interview methods, the experiences of 17 home visiting service provider managers were examined. The study results suggest that the marketization of LTC services faces several challenges. Some of the stakeholders in the field, such as home visiting service providers, care workers, and older clients, appear to employ unlawful activities or unprincipled behaviors to maximize their individual interests. The results also suggest that the unprincipled behavior, unlawful activities, and financial problems that service providers face contribute to low quality care services. Future studies should explore these issues using larger samples of service users and providers.